Study on the Deterioration Level of Piping System in Old and Heritage Building in Batu Pahat, Johor - ABD RAZAK, NIK MUHAMAD AFIQ HAKIME; SYED MOHAMAD, Ts. SYED BURHANUDDIN HILMI (Recent Trends in Civil Engineering and Built Environment, 2021)
The piping systems are an important aspect of the building since water cannot be distributed evenly throughout the structure without them. Because water is a crucial and valuable resource for humans, structural deterioration has created challenges not only to daily life but also to a sustainable society. The purpose of this research is to learn about the maintenance work on the Deterioration Level of Piping System in Old and Heritage Buildings in Batu Pahat, Johor. The valuation used to know the deterioration level are base on JKR Existing Building Inspection Guidelines (JKR 21602 - 0004 – 13). From this research, most of this selected building are being monitored by inexperienced people so most of the problems occur at the building they need to get consult from experts such as engineer from Malaysian Public Works Department. The “Physical State Level Matrix Analysis of Building Components and Priority Level of Maintenance Action” can be used to determine the level of physical condition of a building. Because the maintenance level of this selected building is quite good, the level of deterioration of the piping system in historic and heritage buildings in Batu Pahat, Johor is very low, according to this study. For the future study need to expand the scope of study and Research also needs a contributing approach significantly to explain maintenance concepts related to Production and Operations Management.